2021
DOI: 10.1186/s13047-021-00487-3
|View full text |Cite
|
Sign up to set email alerts
|

Children should be seen and also heard: an explorative qualitative study into the influences on children's choice of footwear, their perception of comfort and the language they use to describe footwear experiences

Abstract: Background Footwear has an essential role including protection of the feet, overall performance, foot health and potentially, supporting normal development of the foot. In addition to these physical aspects which may influence choice of footwear design, there are psychological influences on what a person chooses to wear. The concept of footwear ‘comfort’ spans physical and psychological perceptions of comfort in adults. However, there is little understanding of what influences children’s footwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Footwear comfort is highly valued by students and parents when selecting the shoes, they, or their children, choose to wear to school. These findings are consistent with studies performed in primary school aged children [ 8 , 25 ], as well as adult runners [ 15 , 18 ] and adults with inflammatory arthropathies [ 17 , 33 ]. Parents of secondary school students consider their child’s opinion very important when selecting shoes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Footwear comfort is highly valued by students and parents when selecting the shoes, they, or their children, choose to wear to school. These findings are consistent with studies performed in primary school aged children [ 8 , 25 ], as well as adult runners [ 15 , 18 ] and adults with inflammatory arthropathies [ 17 , 33 ]. Parents of secondary school students consider their child’s opinion very important when selecting shoes.…”
Section: Discussionsupporting
confidence: 91%
“…It is likely that parent and peer opinion are contributors to the selection of school footwear in adolescents. There is a need for greater understanding and consideration of child and adolescent opinions in footwear research [ 24 , 25 ]. Exploring what secondary school students, as well as parents of secondary school students, consider important when choosing school footwear requires investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A study of younger women’s perceptions of dress shoes identified ten criteria which differentiated between comfortable and uncomfortable shoes, the strongest being absence of pain, feeling, sound, and texture [ 17 ]. Finally, in a qualitative study of children, the adjectives soft and padding were most frequently used to describe comfortable shoes, while hard, tight, loose and heavy were used to describe uncomfortable shoes [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…For students, appearance of the shoe and comfort were the most important factors when selecting the shoes worn to school. The perception of comfort may be in uenced by the appearance of the shoe as well as individual physiological factors, gender, wear time and psychosocial and developmental needs (24,25,34). As adolescence is a period of signi cant physical and psychosocial change, clothing, and by extension footwear, may provide adolescents with an opportunity to express their identity (35) which may go some way to explaining the high value placed on appearance by our cohort.…”
Section: Discussionmentioning
confidence: 96%
“…It is likely that parents' opinions are a major contributor to the selection of school footwear in adolescents. There is a need for greater understanding and consideration of child and adolescent opinions in footwear research (24,25). Exploring what secondary school students, as well as parents of secondary school students, consider important when choosing school footwear requires investigation.…”
Section: Introductionmentioning
confidence: 99%